Literary Literacy Among the Younger Generation: Reading More Deeply and Meaningfully - Masruroh, Mia; Nurjanah, Nunuy; Ahmad, Ali Monas (International Journal of Language and Culture, 2025)
Literacy is a very important aspect of life, as it enables access to various types of information. However, among the younger generation, literacy is rarely sought and tends to be neglected. The purpose of this study is to describe the influence of literature on literacy among the younger generation, to develop critical thinking skills through literary literacy, and to identify efforts to increase awareness of literary literacy among the younger generation. The research method used is a descriptive qualitative approach. Data collection techniques in this study include a literature review and the distribution of questionnaires to respondents regarding issues examined in the research, which will produce efforts to maintain literary literacy among the younger generation, identify literary works that are attractive to the younger generation, and determine media preferred by the younger generation to encourage their interest in literary literacy.